Family Resources in Determining Maternal Mental Health and Parenting Style in Predicting Child Behavioral Problems - Shaari, Fauziah; Teoh, Hsien Jin; Sinniah, Dhachayani (Faculty of Psychology, Universitas Surabaya, 2007)
This study examines the effect of family resources in predicting maternal health and her pa- renting style resulting in behavioral problems in children. The study is based on a sample of 40 moth- ers with children ages between 7-12 years old from surrounding Klang Valley. The hypothesis could be that children behavioral problems are due to the maternal parenting style. Inadequacy in family re- sources predicts directly or indirectly the mental health of mothers and her parenting style. This could be due to the direct effects of family resources on the maternal mental health. Kajian ini meneliti pengaruh sumber daya keluarga dalam memprediksi kesehatan ibu dan gaya pengasuhannya yang menghasilkan perilaku bermasalah anak. Sampel (N = 40) adalah ibu dengan anak berusia antara 7-12 tahun dari daerah Klang Valley. Hipotesisnya adalah perilaku bermasalah anak disebabkan oleh gaya pengasuhan ibu. Kurangnya sumber daya keluarga memprediksi secara langsung atau tak langsung kesehatan mental para ibu dan gaya pengasuhannya. Ini mungkin disebabkan oleh pengaruh langsung sumber daya keluarga terhadap kesehatan mental ibu.